Oil in the New World Order - Anas H. Hamed (International Institute of Islamic Thought, 1997)
This readable and informative book discusses recent and expected future developments in the oil industry. It is a compendium of ten articles by academics and industry experts. In the introduction, the editors argue that the international oil industry is a peculiarly volatile industry. Oil prices are very sensitive to crises in the Middle East, where two-thirds of the world's oil reserves are located, where half of the internationally traded oil is produced, and where the cost of production is the lowest in the world. They maintain that, due to the inherent inelasticity of both demand and supply of crude oil and high price volatility, markets have never worked for oil industry efficiently. Consequently, there has always been some son of market order. The editors provide a survey of the different orders that prevailed in the past, such as John D. Rockefeller's monopoly through the Standard Oil Trust, the dominance of the vertically integrated Seven Sisters, and OPEC. The current oil order, according to the authors, is the Saudi-American regime, which emerged after the Jraqi invasion of Kuwait and the subsequent Desert Storm. This regime, which combines huge Saudi oil production capacity with American military might, has replad OPEC. The editors do not expect it to last long, because the new world order following the collapse of the Soviet Union may give rise to a new oil regime independent of the Saudi-American regime: the Commonwealth of Independent States has a potential of huge oil reserves that can be produced at a low cost ...